2021
DOI: 10.3390/cancers13112523
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacological Analysis through a Bioinformatics Approach of Novel NSC765600 and NSC765691 Compounds as Potential Inhibitors of CCND1/CDK4/PLK1/CD44 in Cancer Types

Abstract: Cyclin D1 (CCND1) and cyclin-dependent kinase 4 (CDK4) both play significant roles in regulating cell cycle progression, while polo-like kinase 1 (PLK1) regulates cell differentiation and tumor progression, and activates cancer stem cells (CSCs), with the cluster of differentiation 44 (CD44) surface marker mostly being expressed. These oncogenes have emerged as promoters of metastasis in a variety of cancer types. In this study, we employed comprehensive computational and bioinformatics analyses to predict dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The anti-cancer activity of fostamatinib was also evident against head and neck squamous cell carcinoma [103], hepatocellular carcinoma [104], breast cancer [105], and diffuse large B cell lymphoma [106] cell lines. Moreover, a fostamatinib derivative, NSC765691, also exhibited antiproliferative activity against the panel of NCI-60 cell lines [107]. The drug was also shown to have significant clinical activity when treating non-Hodgkin lymphoma and chronic lymphocytic leukemia patients [108].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-cancer activity of fostamatinib was also evident against head and neck squamous cell carcinoma [103], hepatocellular carcinoma [104], breast cancer [105], and diffuse large B cell lymphoma [106] cell lines. Moreover, a fostamatinib derivative, NSC765691, also exhibited antiproliferative activity against the panel of NCI-60 cell lines [107]. The drug was also shown to have significant clinical activity when treating non-Hodgkin lymphoma and chronic lymphocytic leukemia patients [108].…”
Section: Discussionmentioning
confidence: 99%
“…Potential SJ10 target genes were predicted using an open-source web tool based on the Prediction of Biological Activity Spectra (PASS) [ 44 ] ( , accessed on 17 August 2021). In addition, we explored the Swiss target prediction tool ( , accessed on 17 August 2021), a web-based algorithm that uses the principle of similarity to predict drug targets of bioactive small molecules [ 45 , 46 ] as an independent tool to further validate the predicted potential target genes of SJ10 ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…By this time, several authors have suggested different sets of key genes (KGs) to explore molecular mechanisms and pathogenetic processes of CRC progression [ 14 45 ] in which some studies have employed multiple datasets to identify CRC-causing KGs [ 15 17 , 22 , 25 , 26 , 31 , 32 , 37 , 40 43 , 46 49 ]. Few studies also explored their suggested KGs-guided candidate drug molecules for the treatment against CRC [ 14 , 37 , 40 42 , 50 59 ]. However, their published data did not display any common KGs as well as common drug molecules (see Additional file 1 : Table S1) in all studies.…”
Section: Introductionmentioning
confidence: 99%